2016
DOI: 10.2320/matertrans.m2015260
|View full text |Cite
|
Sign up to set email alerts
|

Board Level Drop Reliability of Epoxy-Containing Sn-58 mass% Bi Solder Joints with Various Surface Finishes

Abstract: Board-level drop reliability testing under JEDEC (Joint Electron Device Engineering Council) drop conditions was conducted for lowtemperature Sn-58 mass%Bi solder joints. The effects of surface finish and the number of reflow processes (one, three, or five) on the drop reliability of the Sn-58Bi joints were evaluated. Three types of surface finishes were used including electroless nickel immersion gold (ENIG), electroless nickel electroless palladium immersion gold (ENEPIG), and organic solderability preservat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 12 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%. In addition, the suppress effect of the IMC was observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder.…”
Section: 22mentioning
confidence: 77%
See 1 more Smart Citation
“…Ma and Wu [105] reported that the thickness of total IMC layers decreased by 56.31% compared with the plain Sn5-8Bi-0.7Zn solder joint when the doping of GNSs was 0.114 wt%. In addition, the suppress effect of the IMC was observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder.…”
Section: 22mentioning
confidence: 77%
“…Meanwhile, Yang et al [106] pointed out the UTS of Sn-Bi + 0:07 wt% composite solder had no obvious change compared with the plain solder, and the elongation and creep properties show a great improvement. Moreover, the improvement phenomenon of mechanical properties is observed by the other researchers due to the doping of GNSs [36,38,106] and epoxy [59,60] into Sn-Bi solder. [50] demonstrated that the doping of TiO 2 could have resulted in the refinement of microstructure of Sn-0.7wt%Cu-0.05 wt%Ni solder by the fabricate process of microwave sintered and the homogeneous (Cu, Ni) 6 Sn 5 intermetallics appear in the grains of particles.…”
Section: Mechanical Propertiesmentioning
confidence: 82%
“…Addition of nanoparticles or fibers like CNT, Y 2 O 3 , Al 2 O 3 , ZrO 2 , TiO 2 , Cu, and Ni to solders is another approach [23][24][25][26][27][28]. The epoxy-containing solders, which form an epoxy layer over the solder fillet, is also helpful to enhance shear strength and drop reliability [29][30][31][32][33]. Therefore, in this paper, we would like to introduce the significant results corresponding to the melting temperature, spreading and wetting, microstructure, inter-metallic thickness, and mechanical properties of Sn-Bi solder upon alloying and nanoparticle addition.…”
Section: Effect Of Alloying Addition On the Melting Temperature Of Sn-bi Soldermentioning
confidence: 99%
“…It was found that the number of drop impacts coincided with the shear failure energy trend [31]. Lee et al [29] investigated the drop reliability of epoxy-containing Sn-58%Bi solder joints with various surface finishes in the board level. The presence of epoxy in the Sn-58%Bi solder slightly improved the drop reliability for ENIG and ENEPIG surface finishes compared to the Sn-58%Bi solder joints without epoxy.…”
mentioning
confidence: 99%